Solitary Splenic Hydatid Cyst - MERAD, Zakaria (Journal of Clinical and Diagnostic Pathology, 2021)
Splenic hydatid cyst is very rare, caused by the parasite echinococcus granulosus. Humans are considered an accidental intermediate host in the development of the parasite cycle. It poses a diagnostic dilemma with other cystic masses despite improved medical imaging techniques often requiring exploratory surgeries for fear of missing out on a malignant tumor. Total or partial splenectomy remains the treatment of first choice and the most effective. We report a case of solitary splenic hydatid cyst and discuss the different differential diagnoses and therapeutic modalities.
Keywords: Macroscopic; hydatid; cyst; echinococcus granulosus; spleen